(untitled) (Bangladesh Journal of Urology, 2022)
Objective: We wanted to evaluate the efficacy and safety of a new treatment of Oligosmetastatic prostate cancer (OMPC) with multimodal approach including local primary tumor therapy, in the form of Cytoreductive Prostatectomy, metastasis-directed therapy (MDT), and hormonal therapy . Methods: We reviewed data of patients with Oligometastatic Prostate Cancer(OMPC) at diagnosis treated in our institutions with ADT and followed by Cytoreductive Prostatectomy (CP) with or without metastases-directed radiotherapy. In this prospective cohort study, 19 patients underwent Cytoreductive radical Prostatectomy and routine Lymphadenectomy, ADT with Degarelix, Aberateron and Prednisolone in the form of neoadjuvant setting during the period of Jan 2016 - March 2021. Of these,05 patients (26.31%) received stereotactic body radiation therapy (SBRT) to all metastatic sites as a MDT in addition to above protocol. Results: The median follow-up period was 46.2 months. Perioperative outcomes, clinical progression, and cancer-specific mortality (CSM) were evaluated. Median age was 72 yr. Median operative time, blood loss, and length of hospitalization were 176 min, 850 ml, and 6 d, respectively. Overall, two patients (10.52%) experienced grade 3 complications in the postoperative period. All received blood transfusions. Overall, 15 (78.94%) and 8 (42.10%) patients had lymph node invasion and positive surgical margins, respectively. Adjuvant Radiation Therapy and androgen deprivation therapy was administered to all 8 patients (42.10%)who confirmed margin Positive status. Of the 19 patients, the 3-year castration-resistant prostate cancer (CRPC)-free survival and cancer-specific survival was100%. Our findings support the safety and effectiveness of Cytoreductive Prostatectomy (C P) in a highly selected cohort of PCa patients with bone metastases and long-term follow-up Conclusion: This Prospective cohort revealed the feasibility of combining ADT and Cytoreductive prostatectomy and metastasis-directed radiotherapy for newly-diagnosed Oligometastatic Prostatic Cancer. This treatment strategy has the potential to delay the progression to CRPC. Bangladesh J. Urol. 2021; 24(2): 146-154